Learner-centered digital competence development for practical chemistry learning in vocational education contexts - Khanh, Lu Bao; Bao, Huynh Gia; Ninh, Tran Trung (Journal of Education and e-Learning Research, 2026)
Digital competence is becoming a fundamental skill for 21st-century learners, especially in vocational education, where practical and technical skills are crucial. The study focuses on developing learner-centered online competence among students involved in work-based chemistry learning in vocational settings. It considers the contributions of leaders, teachers, and learners in supporting a digitally competent learning environment. The research sample included 80 vocational students. Data collection involved pre- and post-intervention assessments, surveys, observations, and semi-structured interviews. The learning intervention consisted of student-focused tasks such as virtual lab sessions, group online experiments, and self-guided data analysis tasks, with teachers guiding and instructing students. Quantitative analysis using paired t-tests and ANCOVA revealed significant improvements in students’ digital competence scores (p < 0.001) and enhanced practical laboratory performance. The most notable improvement was in Teacher Facilitation (TF) (Pre: 3.60; Post: 4.30). The highest paired t-test value was in Software Proficiency (SP) (t = 9.76, p < 0.001). Qualitative findings indicated increased motivation, autonomy, and engagement, with students reporting higher confidence in digital chemistry experiments. The research emphasizes institutional support for teacher training and digital tools, demonstrating that a competency-based, learner-centered approach effectively develops digital and practical skills essential for modern vocational chemistry education.